2016
DOI: 10.1080/13504851.2016.1213356
|View full text |Cite
|
Sign up to set email alerts
|

Adding value through the mechanization of post-harvest cassava processing, and its impact on household poverty in north-eastern Zambia

Abstract: This article investigates the impact of adopting a mechanized cassava processing system on household poverty levels in Zambia. An Foster, Greer and Thorbecke (FGT) poverty measure was used to compare poverty levels among households using a mechanized cassava processing system against those households using a nonmechanized process. Based on the FGT poverty measure's specifications, a significantly lower poverty status of 49% was found among households using the mechanized process when compared to the 58% found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
1
5
0
Order By: Relevance
“…These results on the effect of land ownership and enterprise diversification into livestock farming were in line with prior expectations. The positive relationship between animal husbandry and cassava production could indicate that the farmers' decisions were influenced by the understanding that they can take advantage of the multipurpose use of cassava for livestock feed production (Abass et al, 2013). This finding concurs with Manganyi et al ( 2023), who found that cassava production was associated with livestock farming in three different regions in South Africa due to the crop's dual purpose in rural households.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These results on the effect of land ownership and enterprise diversification into livestock farming were in line with prior expectations. The positive relationship between animal husbandry and cassava production could indicate that the farmers' decisions were influenced by the understanding that they can take advantage of the multipurpose use of cassava for livestock feed production (Abass et al, 2013). This finding concurs with Manganyi et al ( 2023), who found that cassava production was associated with livestock farming in three different regions in South Africa due to the crop's dual purpose in rural households.…”
Section: Resultssupporting
confidence: 79%
“…One such water-saving crop that has been promoted as having unexplored potential in addressing the forthcoming water insecurity is cassava (Abass et al, 2017). According to FAO (2018), there has been wide recognition of cassava as a choice crop in the context of climate change adaptation strategies, particularly in eastern and southern African countries that regularly endure sustained periods of drought.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond being a staple food crop globally (mainly for rural impoverished households), cassava poses a great potential for generating income through the sale of fresh cassava tubers and other processed derivatives. According to [8], in several countries such as Nigeria, Brazil, and Thailand, value addition has shown immense potential to enable cassava growers, processors, and/or traders to earn premium prices within the cassava value chain as opposed to selling the perishable tubers. Furthermore, cassava's ability to yield significant edible biomass per unit of land can potentially increase income.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, flash dryers must be energy-efficient (Chapuis et al, 2018). Abass et al (2017a) and Abass et al (2017b) have shown that the adoption of a mechanized cassava processing system can transform primary production activities, in turn leading to higher incomes and reduced poverty levels among cassava farmers in many African countries, including Zambia and Uganda. IITA (2006) asserted that Nigeria needs more than 300 units of flash dryers with a capacity of 3-5 ton/day to meet the current demand for cassava flour.…”
Section: Introductionmentioning
confidence: 99%